Intervensi Sosial dan Dukungan Keluarga Dalam Mengatasi Kecanduan Judi Online di Kalangan Remaja - Rukminiarti, Rukminiarti; Safitra, Linda; Ledyawati, Ledyawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Online gambling addiction among adolescents has become an increasingly alarming social issue, including in Talang Ulu Village, North Bengkulu. This study aims to analyze the role of families and communities in addressing this issue using the social fact approach and Structural Functionalism theory. A qualitative descriptive method was employed, with data collected through interviews, observations, and documentation involving families, community leaders, and adolescents. The findings reveal that families play a crucial role as agents of socialization by instilling moral values, providing emotional support, and supervising behavior in a non-coercive manner. In parallel, community leaders and village authorities contribute through social assistance as a form of social control. Collaboration between family and community proves effective in mitigating online gambling addiction among youth. The study concludes that strong synergy among social elements is essential to maintaining societal harmony amidst modernization. The implications highlight the need to strengthen family values and community involvement to prevent and address deviant behavior among adolescents.